Clinicopathological Features and RB1 Gene Polymorphism in Sudanese Retinoblastoma Patients (Journal of Cancer Research Updates, 2025)
Background: Retinoblastoma is a highly aggressive eye cancer affecting infants and young children, with outcomes dependent on early diagnosis. Mortality remains high in low-resource settings. This study aimed to characterize retinoblastoma among Sudanese patients, including an analysis of clinicopathological features and the status of RB1 gene polymorphisms.Material and Methods: This is cross-sectional study included 99 Sudanese patients diagnosed with retinoblastoma in Khartoum Teaching Eye Hospital and Mecca Eye Complex. Clinicopathological features and demographic data were retrieved from patient’s medical records and histopathology Laboratory Information System (LIS). Genomic DNA was isolated from formalin fixed paraffin embedded (FFPE) retinoblastoma tissue blocks. Detection of RB 1 gene polymorphism was conducted through Polymerase Chain Reaction (PCR). BLAT search genome used to compare the results of breakpoint sequencing with a reference genomic sequence.Results: Total of 99 retinoblastoma patients were included, (53.5%) were female and (46.5%) were male, with (79.8%) having unilateral lesions and (20.2%) bilateral. Nerve invasion was present in (44.4%) of the cases. Half of patients were diagnosed at advance stage (T4) (58.6%) and at high grade were (Grade 3) (69.7%). (15%) of the cases were from Damazin state, followed by Nyala (13.1%).Conclusion: Detection of retinoblastoma in Sudanese patients often occurs at advanced stages and grades, leading to poorer clinical outcomes. Genetic testing is crucial to identify individuals predisposed to this illness, enabling early intervention and management.